Pengembangan Produk Mainan Huruf Arab Braille Dengan Menggunakan Metode Quality Function Deployment - Khairi, Aziati Ridha; Hermana, Budi (Riset Sinergi Indonesia, 2023)
Increasing the ability of blind children can be done through by reading skills. A total blind person is in desperate need of braille to be able to read and get important information. Not only the letters of the Braille alphabet, the blind are also expected to be able to understand the Arabic braille letters, one of which is to facilitate reading Braille Quran. The purpose of the study are identify customer needs, technical characteristics, product specifications and product design, find out the material used, and estimate the total cost to make one product. Products are designed using Quality Function Deployment (QFD) and product visualization using CATIA. Customer needs for arabic letter braille toys are interesting, not boring, the material used is non-toxic, the material is not easily broken, not easily damaged, toys are easily stored, not too big, not heavy, easy to use, not harmful when used, and multifunctional toys. The product technical characteristics are shape, material type, weight, length, width, and height. The specifications of product are box shape design, the material used is Dutch teak, product size is 27 x 19.5 x 15 cm, product weight is 979gr. The estimated total cost for braille Arabic toy is Rp.131,936.